Fake money, blue smoke eaudiobook - Haven, Josh (HighBridge Audio, 2022)
When former platoon sergeant Matt Kubelsky is paroled from Ray Brook Federal Correctional Institute in upstate New York, he's surprised to find his ex-girlfriend waiting for him out in the parking lot. An ex-girlfriend he's spent years pining for after she dumped him. An ex-girlfriend who wonders if her apparently criminally-hardened ex-boyfriend can help her out of some extra-legal difficulty of her own. During the years Matt was in prison, Kelly Haggerty discovered she couldn't earn a satisfactory living as an artist, so she turned her artistic talents to counterfeiting foreign currency-and ended up embroiled in an international money laundering intrigue. Now she hopes she can get herself out of trouble with a cleverly-plotted theft and one last enormous score. The missing ingredient is someone Kelly can trust to do the dirty work, recruiting career criminals who won't flinch at the opportunity to make good money by whatever means necessary. And Matt is happy to oblige, as it seems like the perfect opportunity to settle the score with the men responsible for ruining his life and putting him away for a crime he didn't commit. The heist-a horseback robbery of valuable artwork from a speeding Amtrak train-seems to be going perfectly, until one of the players starts to suspect he's been paid in counterfeit bills . . .